Analisis perhitungan, pelaporan pajak pertambahan nilai pada pt. ryan samudra adijaya di samarinda - Nini Raisa Simbolon; Yunus Tete Konde; Salmah Pattisahusiwa (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
PT Ryan Samudra Adijaya is a company engaged in river or sea transport services for the territory of the Republic of Indonesia, which has been confirmed as a Taxable Entrepreneur (PKP) by the Directorate General of Taxation through the local Tax Office, to collect, deposit and report Value Added Tax (VAT) on Taxable Services (JKP) or Taxable Goods (BKP). Purpose of this study The purpose of this study is to determine how the calculation of Value Added Tax (VAT) by determining the tax base (DPP) on a fiscal basis and report it to the Tax Office where registered in accordance with the VAT Act No.42 of 2009, especially in the field national shipping services business. The results of this study, that PT.Ryan Samudra Adijaya in performing calculations and reporting value added tax is not in accordance with Law no. Since the company in calculating the VAT from foreign currency (USD) still exists using the middle rate of Bank Indonesia (BI), thus causing the difference of VAT is VAT overpay, therefore the researcher recommends that the VAT calculation if using the eyes foreign currency must use the tax rate in accordance with the Minister of Finance Decree.